An immunogenic phenotype in paternal antigen‐specific CD8+ T cells at embryo implantation elicits later fetal loss in mice. Issue 8 (27th June 2017) - Moldenhauer, Lachlan M; Diener, Kerrilyn R; Hayball, John D; Robertson, Sarah A
Abstract : Central to pregnancy success is a state of T cell tolerance to paternal antigens, which is initiated at conception. The role and regulation of specific phenotypes of CD8 + T cells in mediating pregnancy tolerance is not clear. This study aimed to investigate the impact on pregnancy outcome of altering the cytokine environment during maternal CD8 + T cell priming in early pregnancy. Transgenic Act‐mOVA male mice were mated to C57BL/6 (B6) females to generate fetuses expressing ovalbumin (OVA) as a model paternal antigen. OVA‐reactive CD8 + OT‐I T cells were activated in vitro with OVA in the presence of either transforming growth factor‐β1 (TGFB1) plus interleukin‐10 (IL10), or IL2, to mimic normal or dysregulated uterine conditions, respectively, and transferred into pregnant mice on gestational day 3.5. OT‐I T cells activated with TGFB1 and IL10, like naive OT‐I T cells, did not alter embryo implantation or fetal viability. In contrast, OT‐I T cells activated with IL2 caused extensive fetal loss manifesting in mid‐gestation. IL2‐activated OT‐I T cells expressed less FOXP3 and higher interferon‐γ (IFNG) than cells activated with TGFB1 and IL10. Fetal loss did not occur in females mated with B6 males, demonstrating the antigen specificity of fetal loss, and was not abrogated by maternal genetic C1q deficiency indicating a mechanism independent of antibody‐mediated cytotoxicity. These data indicate that alternative phenotypes generated in maternal CD8 + T cells at the time of priming with paternal antigens can impact pregnancy outcome, such that inappropriate activation of CD8 + T cells before implantation is capable of causing antigen‐specific fetal loss later in pregnancy.